The comparison of two domain repartitioning methods used for parallel discrete element computations of the hopper discharge. (June 2015) - Markauskas, Darius; Kačeniauskas, Arnas
Highlights: Two methods are employed for dynamic domain decomposition of hopper discharge. Implementation of the k-way graph partitioning method in DEM codes is more complex. A higher speed-up is measured, applying the recursive coordinate bisection method. Parallel efficiency of 0.87 is attained simulating 5.1 × 10 6 particles on 2048 cores. Abstract: The paper presents an application of two domain repartitioning methods to solving hopper discharge problem simulated by the discrete element method. Quantitative comparison of parallel speed-up obtained by using the multilevel k-way graph partitioning method and the recursive coordinate bisection method is presented. The detailed investigation of load balance, interprocessor communication and repartitioning is performed. Speed-up of the parallel computations based on the dynamic domain decomposition is investigated by a series of benchmark tests simulating the granular visco-elastic frictional media in hoppers containing 0.3 × 10 6 and 5.1 × 10 6 spherical particles. A soft-particle approach is adopted, when the simulation is performed by small time increments and the contact forces between the particles are calculated using the contact law. The parallel efficiency of 0.87 was achieved on 2048 cores, modelling the hopper filled with 5.1 × 10 6 particles.